Alexithymia in chronic and episodic migraine: a comparative study. (4th May 2017) - Galli, Federica; Caputi, Marcella; Sances, Grazia; Vegni, Elena; Bottiroli, Sara; Nappi, Giuseppe; Tassorelli, Cristina
Abstract: Background : Alexithymia is a term used to describe a disorder where patients have difficulty in expressing their own feelings in words. Aims : The analysis of alexithymia in patients suffering from chronic migraine (CM) or episodic migraine (EM) compared to healthy controls. Methods : Two clinical samples formed by 80 CM patients (21 males and 59 females, mean age: 44.65) and 44 EM patients (8 males and 36 females, mean age: 42.18) were enrolled. A group of 67 healthy subjects served as controls (26 males and 41 females, mean age: 41.21). All subjects were requested to fill in the 20-item version of the Toronto Alexithymia Scale (TAS-20). Results : We found a statistically significant difference between groups in Factor 1 (difficulty in describing feelings), F (2, 191) = 7.96, p < 0.001, and in TAS total, F (2, 191) = 5.37, p = 0.005. Post-hoc analyses revealed that CM patients had higher scores in TAS factor 1 and in TAS total than healthy controls. There were no significant differences between CM and EM patients, even if CM sufferers reported a trend towards higher scores in each TAS factor as well as in TAS total. Conclusions : Alexithymia emerges as a potential characteristic trait of migraine, regardless of disease severity.